Perancangan User Experience Aplikasi Pengelolaan Pelatihan Program Pekerti dan Applied Approach dengan Metode Human-Centered Design (Studi Kasus: Universitas Brawijaya) - Muhammad Rizaldi; Denny Sagita Rusdianto; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Lecturers are a profession that has an important role in the world of higher education, they are professional educators as well as scientists who provide their knowledge to college students. Therefore, in carrying out their duties, lecturers must have a certificate as professional lecturers, which can be obtained from Pekerti AA training. Pekerti AA training is a training program for lecturers that focuses on improving the quality of learning at the university where they work. The Pekerti AA training management application will focus on making it easy for training applicants to register and find all information related to training, as well as making it easier for the committee to manage applicant data. In the process of designing the Pekerti AA application, a good user experience is needed. To get a good user experience, a human-centered design development method is needed. The testing procedure necessitates usability testing and also filling out the UE questionnaire. By involving five respondents, the test results were obtained, namely a value of 89% for the value of effectiveness and a value of 0.09174 goals per second for the value of efficiency. A value of 80, with those included in grade A-, means good and acceptable. The results of the UEQ show that attractiveness and stimulation get excellent status, while perspicuity, efficiency, dependability, and novelty get good status.